The Morphology of Early Towns in Malay Peninsula - Mohmad Shukri, Sharyzee; Hussaini Wahab, Mohammad; Che Amat, Rohayah; Taib, Idris; Ismail, Syuhaida (International Journal of Engineering and Technology, 2018)
Malay Peninsula has a very compelling socio geographical, cultural history and town setting comprises historical sites, fortress and early towns that has formed an evolution of the urban sprawl. The history of the early towns on the Malay Peninsula goes as far back as the beginning of the ancient Malay kingdom of Lembah Bujang and Langkasuka; and maybe far before that period. Early Malay towns in Malay Peninsula (currently known as Peninsular Malaysia) have unique characteristics in terms of architecture urban form and history. The morphology study of towns in Malay Peninsula have found characteristics of urban form and setting dating from 5000 BC maybe earlier to 19th century may be classified into four phases of pre-modern settlements cycles. This research employs qualitative approach that encompasses of literature review of scholarly articles and reports, in-depth interview and structured observation. Based on the historical and physical evidences that are still exist, thirteen (13) early town will be selected as a study area. This paper present the finding of urban morphology and characteristic in a chronicle of urban form and setting in the Malay Peninsula dating from 5000 BC up to the 19th century.